2006
DOI: 10.1096/fj.05-4944fje
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis of blood microvessels from PDGF‐B and PDGF‐Rβ mutant mice identifies novel markers for brain pericytes

Abstract: Normal blood microvessels are lined by pericytes, which contribute to microvessel development and stability through mechanisms that are poorly understood. Pericyte deficiency has been implicated in the pathogenesis of microvascular abnormalities associated with diabetes and tumors. However, the unambiguous identification of pericytes is still a problem because of cellular heterogeneity and few available molecular markers. Here we describe an approach to identify pericyte markers based on transcription profilin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
145
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 175 publications
(156 citation statements)
references
References 78 publications
(90 reference statements)
9
145
0
Order By: Relevance
“…Our observation that PDGFRa expression was low in thymic perivascular cells of adult mouse is consistent with other studies showing that neural crest-derived cells within the parenchyma of the thymus downregulate the expression of PDGFRa, whereas they maintain PDGFRb expression (Foster et al 2008;Müller et al 2008). A similar downregulation of PDGFRa has also been observed during pericyte differentiation in the brain (Bondjers et al 2006). Migration of neural crests into the thymus during embryogenesis and their differentiation into perivascular cells has been demonstrated (Foster et al 2008;Müller et al 2008).…”
Section: Discussionsupporting
confidence: 92%
“…Our observation that PDGFRa expression was low in thymic perivascular cells of adult mouse is consistent with other studies showing that neural crest-derived cells within the parenchyma of the thymus downregulate the expression of PDGFRa, whereas they maintain PDGFRb expression (Foster et al 2008;Müller et al 2008). A similar downregulation of PDGFRa has also been observed during pericyte differentiation in the brain (Bondjers et al 2006). Migration of neural crests into the thymus during embryogenesis and their differentiation into perivascular cells has been demonstrated (Foster et al 2008;Müller et al 2008).…”
Section: Discussionsupporting
confidence: 92%
“…36,37 We analyzed expression of Eltd1, Gpr116, Ramp2, Slc9a3r2, Slc43a3, Rasip1 and Hig2;NM_023516 in wild-type and pdgfb Ϫ/Ϫ microvessels by RTQ-PCR, expecting that putative pericyte markers would be significantly down-regulated in the latter. 26,38 As shown in Figure 5B, none of these genes behaved as a pericyte transcript. Hig2;NM_023516 was downregulated in pdgfb Ϫ/Ϫ microvessels (0.7 fold-change; log 2 ratioϭ Ϫ0.53) but at much lower than expected for a genuine pericyte marker 26 Thus, Hig2;NM_023516 is either expressed in both endothelial cells and pericytes, or is positively regulated in endothelial cells by the presence of pericytes.…”
Section: Expression In Pericyte-deficient Microvesselsmentioning
confidence: 90%
“…26 Total RNA samples were obtained from individual adults or embryos. Real-time quantitative PCR (RTQ-PCR) was performed using a 7300 instrument (Applied Biosystems) and standard protocols and reagents.…”
Section: Isolation Of Microvascular Fragments Rtq-pcr and Transcripmentioning
confidence: 99%
“…5 Similarly, the consequences of pericyte deficiency were examined in brain microvessels by microarray analysis in platelet derived growth factor-B-deficient mice. 6 In a study of human coronary artery segments isolated from explanted hearts of cardiac transplant patients, King et al 7 identified multiple effected gene pathways and further confirmed the microarray findings by immunohistochemical analysis of selected proteins. Downstream gene targets of nitric oxide (NO) have been detected by Bogdan et al 8 however, no studies have been conducted to elucidate the molecular consequences of nitric oxide deficiency.…”
mentioning
confidence: 85%